2000
DOI: 10.1016/s0304-3940(00)00778-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrathecal baclofen on gait control in human hereditary spastic paraparesis

Abstract: The covariation between thigh, shank and foot elevation angles during locomotion was analysed by means of orthogonal planar regression in a patient with pure hereditary spastic paraparesis before and after an intrathecal bolus of baclofen and in seven healthy subjects. The size, shape and spatial orientation of the loop de®ning patient's planar covariation (thigh angle vs. shank angle vs. foot angle) signi®cantly differed from the controls' before baclofen, whereas these features resumed normal characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…This has been observed in level walking [11][12][13] and various other modes of locomotion [14][15][16][17][18][19][20]. As well, this pattern has been shown to persist during locomotion in adults with impairments such as Parkinson's disease [21], spastic paraparesis [22], spinal cord injury [17] and forefoot rheumatoid arthritis [23]. The significance of this planar pattern is that it suggests the central nervous system (CNS) decreases the available degrees of freedom, therefore simplifying locomotor control [12,13,24].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This has been observed in level walking [11][12][13] and various other modes of locomotion [14][15][16][17][18][19][20]. As well, this pattern has been shown to persist during locomotion in adults with impairments such as Parkinson's disease [21], spastic paraparesis [22], spinal cord injury [17] and forefoot rheumatoid arthritis [23]. The significance of this planar pattern is that it suggests the central nervous system (CNS) decreases the available degrees of freedom, therefore simplifying locomotor control [12,13,24].…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies observing locomotion in pathological populations such as Parkinson's disease [21], spastic paraparesis [22], spinal cord injury [17] and forefoot rheumatoid arthritis [23] have shown that planarity of segment elevation angles remains high (above 97%) during level walking. In the current study, similar observations of high planarity during level walking can be seen in the CA group.…”
Section: Intersegmental Coordination During Level Walking and Obstaclmentioning
confidence: 99%
“…In healthy adults, the orientation of the covariation plane is directly related to the mechanical energy cost of walking (Bianchi et al 1998a, b). Restoration of the covariation plane in treated patients with Parkinson's disease or hereditary spastic paraparesis (Dan et al 2000a) also indicates that this parameter reflects the mechanical efficiency of walking. In toddlers, the planar covariation of the elevation angles of the lower limb segments is weak or absent at the very first unsupported steps, but is established over the first few weeks with an orientation in 3D segment space that is similar to the adult one.…”
Section: Mechanics Of Walkingmentioning
confidence: 98%
“…[7]). Whereas the planar covariation analysis of locomotion presents the advantage to follow the evolution of co-ordination of at least three body segments by only one parameter in normal [3] or pathological situations [9,12], the CCF analysis can decipher subtle differences in disto-proximal maturation of temporal coordination. …”
mentioning
confidence: 99%